GMINOWŁADZTWO LELEWELA CZY FEUDALIZM KARAMZINA – USTRÓJ PANUJĄCY NA OBSZARZE RUSI W ŚREDNIOWIECZU - Podolan, Eligiusz (In Gremium. Studies in History, Culture and Politics, 2008)
MEDIEVAL RUTHENIA’S SOCIAL SYSTEM ACCORDING TO LELEWEL AND KARAMZIN: LOCAL GOVERNANCE OR FEUDALISM? S u m m a r y This paper deals with the social systems in medieval Poland and Ruthenia – as described by scholars of the Enlightenment: Joachim Lelewel and Mikołaj Karamzin. The former sees the Slavic lands as dominated by the local governance of the noblemen, with a high share of hereditary, rather than vassal, lands. The latter stresses the influence of feudalism on the development of Ruthenia’s social system because he is keen on erasing the technological and historical differences between present-day Russia and Western Europe. This paper’s author sets out to show the influence of the changing feudal system on the development of Central European countries.